2021
DOI: 10.3390/ijerph18041670
|View full text |Cite
|
Sign up to set email alerts
|

“Shedding Light on Light”: A Review on the Effects on Mental Health of Exposure to Optical Radiation

Abstract: In relation to human health and functioning, light, or more specifically optical radiation, plays many roles, beyond allowing vision. These may be summarized as: regulation of circadian rhythms; consequences of direct exposure to the skin; and more indirect effects on well-being and functioning, also related to lifestyle and contact with natural and urban environments. Impact on mental health is relevant for any of these specifications and supports a clinical use of this knowledge for the treatment of psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 154 publications
(157 reference statements)
1
7
0
Order By: Relevance
“…However, our results have shown that under lower concentrations of UVB exposure (for at least 1 year, including UVB low level and UVB moderate level), the risk of UVB for depression is reduced. These results are similar as previous studies [ 63 , 64 ]. In keratinocytes, UVB light stimulates ROS production.…”
Section: Discussionsupporting
confidence: 94%
“…However, our results have shown that under lower concentrations of UVB exposure (for at least 1 year, including UVB low level and UVB moderate level), the risk of UVB for depression is reduced. These results are similar as previous studies [ 63 , 64 ]. In keratinocytes, UVB light stimulates ROS production.…”
Section: Discussionsupporting
confidence: 94%
“…No evidence that light exposure improves mental health Exposure to bright light is a well-established therapy for seasonal depression 32 and some previous research has found 31 that mental wellbeing is generally associated with light exposure. We investigated this pattern by considering the possible patterns of confounding in a cross-sectional observational sample such as Hungarostudy 2021.…”
Section: Chronotype and Healthmentioning
confidence: 99%
“…A third factor connecting the timing of daily activities to specifically mental health outcomes is exposure to natural light 31 . Light therapy is a widely used intervention to treat depression 32 , but some research indicates that more exposure to natural light is associated with better mental health outcomes even in normal populations [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that electromagnetic radiation of various ranges can have both negative and positive effects on a human organism, in particular, on the nervous and the cardiovascular systems, as well as on the immune and endocrine systems and other internal organs and functional systems [1][2][3][4][5][6] . The aim of this work is to study, using an Automated pulse diagnostic system (APDS), the quantitative effect of optical radiation of the two extreme colors of the optical range (red and blue) on the functional state of the human internal organs in order to continue developing technologies for managing human mental and physiological state 6,7 .…”
Section: Introductionmentioning
confidence: 99%